ANALYSIS OF MONEY UTILIZATION IN THE PERSPECTIVE OF ISLAMIC ECONOMICS: CASE STUDIES AND THEIR IMPLICATIONS - Fajriatussaadah, Nurul; Ali Murtadho; Wahab Zaenuri (Wasīlah: Journal Of Sharia Sciences, 2026)
This study examines the role of money within the framework of Islamic economics and analyzes how Sharia principles influence its utilization in real economic activities. Using a qualitative literature-based approach supported by scholarly books, journal articles, and institutional documents, the research also incorporates comparative case studies from Malaysia, Saudi Arabia, and Indonesia. The findings reveal that Islamic economics views money not merely as a medium of exchange but as an instrument that carries social responsibility and ethical obligations. The application of Sharia principles such as the prohibition of riba, the promotion of risk-sharing, and the encouragement of asset-backed transactions demonstrates the potential to enhance sustainable economic growth, strengthen financial stability, and promote social justice. Although the three countries share common foundational values regarding the function of money in Islamic economic practice, variations in regulatory frameworks and economic priorities lead to different macroeconomic impacts. Nevertheless, all three cases converge on a similar objective: fostering equitable, ethical, and sustainable economic welfare in line with their respective socioeconomic contexts. Keywords : money usage; sharia principles; dan macroenomomic